2015
DOI: 10.1515/frp-2015-0018
|View full text |Cite
|
Sign up to set email alerts
|

The diet of the roe deer (Capreolus capreolus) in the forest ecosystems of Zhytomirske Polesie of the Ukraine

Abstract: The botanical composition of the European roe deer diet in the radioactively contaminated forest ecosystems of Zhytomirske Polesie of the Ukraine was investigated. Deer were caught monthly over a two–year period on three plots in forest habitats typical for Zhytomirske Polesie (fresh and moist mixed coniferous forests and mixed broadleaved forests). An analysis of the stomach contents of hunted deer showed that they consumed leafy as well as leafless stems, grasses, fruits and mushrooms depending on the season… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 4 publications
2
6
0
Order By: Relevance
“…The number of identified taxa is comparable to that found in previous studies on the European roe deer (e.g. Tixier et al 1997;Bartolomé et al 2002;Krasnov et al 2015). For instance, Bartolomé et al (2002), analysing the faecal pellets collected in a natural park located in Spain, found the diet of the European roe deer to be composed of 56 different plants.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…The number of identified taxa is comparable to that found in previous studies on the European roe deer (e.g. Tixier et al 1997;Bartolomé et al 2002;Krasnov et al 2015). For instance, Bartolomé et al (2002), analysing the faecal pellets collected in a natural park located in Spain, found the diet of the European roe deer to be composed of 56 different plants.…”
Section: Discussionsupporting
confidence: 84%
“…The other plants identified in the present study have also been found to be components of the diet of the European roe deer. For example, the consumption of Hedera helix or various species of Rubus has been described in some previous studies (Jackson 1980;Tixier et al 1997;Moser et al 2008;Krasnov et al 2015). These results seem to indicate that the diet of roe deer C. capreolus and that of its subspecies C. c. italicus are similar.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…As highly selective feeders, they are especially sensitive to dietary changes (Toïgo et al 2006, Parker et al 2009. Nevertheless, during the winter months roe deer, like other wild ruminants, have to adapt their nutritional and physiological strategies to the seasonal variation of lower food quality and availability (Gębczyńska 1980, Tixier et al 1997, Arnold et al 2015, Krasnov et al 2015).…”
mentioning
confidence: 99%
“…Lingonberry is a source of food and water for birds (Jacquemart and Thompson 1996) and mammals (e.g. Baltrūnaitė 2001;Jaroszewicz et al 2008;Krasnov et al 2015). Numerous insect and other invertebrate species also feed on V. vitis-idaea, and use lingonberry dwarf-shrubs as shelter.…”
Section: Introductionmentioning
confidence: 99%